Analisis Perceived Quality Produk Handphone Merek Nokia - Suhaji Suhaji (STIE Widya Manggala, 2008)
Quality is one of the importance thing belong to product. Quality is devided into two aspects, objective quality and perceived quality. The important one is quality that perceived by customer (perceived quality). The purpose of this is to know how the perceived quality of Nokia product, so that Nokia becomes the leader vendor in handphone market in Indonesia. The result show that in the customers perception, Nokia has the quality among others. That is shown by the total Perceived Quality in the result analysis.